A qualitative metasynthesis on the sexual health of women who have undergone female genital mutilation or cutting (FGM/C) living in western countries - Emmanuelle Gareau; Andréanne Dufour; Christina Zarowsky; Olivier Ferlatte (SSM: Qualitative Research in Health)
Rationale: Female genital mutilation or cutting (FGM/C) or circumcision can have lasting consequences on survivors' sexual health and is an important public health issue in Western countries due to migration. While some quantitative reviews have examined the psychosexual consequences of FGM/C, survivors’ perspectives remain understudied. Objective: We aim to synthesize existing qualitative data on the experiences of women who have undergone FGM/C and who live in Western countries, focusing on their perspectives regarding sexual health. Methods: A systematic search was performed in six databases to identify relevant qualitative or mixed-method empirical articles that pertain to sexual health-related matters and provide direct quotations from adult participants who have undergone FGM/C and who live in Western countries. Data was thematically synthesized using QSR's Nvivo14. Results: We synthesized data from 27 articles and identified three overarching themes related to the control of women's bodies and sexuality: 1) Rigid sexual and gender norms as obstacles to sexual fulfillment, 2) FGM/C as both creator and annihilator of sexual identity and feeling, 3) The hegemony of the taboo related to FGM/C and sexuality leading to the sexual subjugation of women. Conclusion: This study identified macro (e.g., sexual and gender norms, roles, diktats) and micro-level factors (e.g., FGM/C itself, sexual expectations) influencing the sexual health of women who have undergone FGM/C and who live in Western countries. Future research, health promotion initiatives, and psychosexual care should consider the various dimensions of sexuality when addressing FGM/C survivors’ sexual health.